Low-frequency (ELF–VLF) radio atmospherics study at the Ukrainian Antarctic Akademik Vernadsky station - Shvets, A.V.; Nickolaenko, A.P.; Koloskov, A.V.; Yampolsky, Yu.M.; Budanov, O.V.; Shvets, A.A. (Український антарктичний журнал, 2019)
This paper describes the results of the atmospherics measurements in the extremely low-frequency (ELF) and very low-frequency (VLF) frequency ranges performed at the Akademik Vernadsky station (64.26W; 65.25S) during February–April 2019. The main objective of the study was the implementation of a single-site technique for monitoring the lower ionosphere parameters and locating globally distributed powerful lightning discharges. У даній статті описано результати вимірювань атмосфериків в діапазонах наднизькочастотних (ННЧ) і дуже низькочастотних (ДНЧ), виконаних на Українській антарктичній станції (УАС) «Академік Вернадський» (64.26 W; 65.25 S) протягом лютого—квітня 2019 року. Основною метою дослідження була реалізація однопозиційного методу для моніторингу параметрів нижньої іоносфери та локації потужних грозових розрядів, розподілених по всій планеті.